2015
DOI: 10.1093/humrep/dev100
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen promotes the survival of human secretory phase endometrial stromal cells via CXCL12/CXCR4 up-regulation-mediated autophagy inhibition

Abstract: This study was supported by the National Natural Science Foundation of China (NSFC) (81471513, 81471548 and 81270677), the Training Program for Young Talents of Shanghai Health System XYQ2013104, the Program for Zhuoxue of Fudan University, and the Program for Creative Talents Education of Key Disciplines of Fudan University. None of the authors has any conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 36 publications
3
78
0
Order By: Relevance
“…A decrease of autophagic activity in ectopic and eutopic endometrial cells leads to less autophagy-dependent degradation of proteins and less programmed cell death. Our previous work also established that autophagy suppression induced by CXCL12 promotes growth of ESCs in vitro (Mei et al 2015). Mediated via the lysosomal degradation pathway, autophagy is responsible for degrading cellular proteins and is currently the only known process for degrading cellular organelles, recycling them to ensure cell survival (Reggiori & Klionsky 2002).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A decrease of autophagic activity in ectopic and eutopic endometrial cells leads to less autophagy-dependent degradation of proteins and less programmed cell death. Our previous work also established that autophagy suppression induced by CXCL12 promotes growth of ESCs in vitro (Mei et al 2015). Mediated via the lysosomal degradation pathway, autophagy is responsible for degrading cellular proteins and is currently the only known process for degrading cellular organelles, recycling them to ensure cell survival (Reggiori & Klionsky 2002).…”
Section: Discussionmentioning
confidence: 94%
“…Our previous work showed that estrogen repressed the autophagy of the ESCs by upregulating CXCL12/CXCR4 signaling, and further promoted ESC growth (Mei et al 2015). In order to analyze the expression of IL15 receptors (i.e.…”
Section: Esc Autophagy Induced By Rapamycin Downregulates Il15 Receptmentioning
confidence: 99%
“…ESCs were purified and cultured from endometrial tissue as previously described (7). The ESCs exhibited 92% purity (Vimentin positive).…”
Section: Methodsmentioning
confidence: 99%
“…To clarify the miRNAome and mRNAome of CXCL12-treated ESCs, cells were treated with 100 ng/ml rhCXCL12 (R&D Systems, Inc., Minneapolis, MN, USA) for 48 h, whereas the control ESCs were cultured with 1% phosphate-buffered saline (PBS; Corning Incorporated, Corning, NY, USA) as the vehicle control. The rhCXCL12 treatment dose and exposure time were selected according to our previous study (7). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation